Takayasu’s Arteritis- An Unusual Cause of Stroke in a Young Patient - Matthew Silver (Western Journal of Emergency Medicine, 2012)
We describe the case of a 28-year-old-male with no significant medical history who presented with right-sided hemiparesis, bruits over the carotid and subclavian arteries and an elevated erythrocyte sedimentation rate. Imaging studies revealed a middle cerebral artery thrombus and inflammatory changes of the carotid and subclavian arteries and aorta. The diagnosis of Takayasu’s arteritis was made and the patient was started on steroids and immunomodulators with good clinical response.